Graphitic carbon nitride nanostructures: Catalysis. (September 2019) - Kong, Lingru; Wang, Jiangcai; Ma, Fengcai; Sun, Mengtao; Quan, Jun
Highlights: The physical structure and properties of g-C3 N4 are introduced in detail. The synthesis methods of g-C3 N4 are reviewed in detail. The various characterization means for g-C3 N4 are systematically summarized. The outstanding applications of g-C3 N4 are introduced photocatalysis reactions. Abstract: The graphitic carbon nitride nanocomposites which possess a graphite-like layered structure have been widely attracted much attention in some applications due to their remarkable catalytic properties. Recent studies have made a surprising breakthrough in developing by adjusting materials and synthesis methods. In this review, the types of graphitic carbon nitride nanostructures and methods used in the synthesis are introduced thoroughly. The various characterization means are systematically summarized and their functions are also clearly explained. Particularly, the outstanding merits of applying graphitic carbon nitride nanocomposites in applications are described by introducing their roles in promoting catalytic reactions efficiency, which are revealed specifically by researching oxygen reduction reactions (ORR), hydrogen evolution reactions (HER), measurement of the gas sensing properties, nitrogen photofixations reactions, degradation of CO2, NO x, 2-propanol, degradation of organic pollutants and photoreduction removal of Cr(VI).